Changes in root‐exudate‐induced respiration reveal a novel mechanism through which drought affects ecosystem carbon cycling. Issue 1 (24th July 2019) - de Vries, Franciska T.; Williams, Alex; Stringer, Fiona; Willcocks, Robert; McEwing, Rosie; Langridge, Holly; Straathof, Angela L.
Summary: Root exudates play an important role in ecosystem response to climate change, but the functional consequences of drought‐induced changes in the quality of root exudates are unknown. Here, we addressed this knowledge gap in a unique experimental approach. We subjected two common grassland species that differ widely in their growth strategies and root systems, the grass Holcus lanatus and the forb Rumex acetosa, to 2 wk of drought. We collected root exudates and soils at the end of the drought and after 2 wk of recovery and readded all root exudates to all soils in a fully reciprocal set‐up to measure root‐exudate‐induced respiration. We found that soil treatment was unimportant for determining root‐exudate‐induced respiration. By contrast, root exudates collected from plants that had experienced drought clearly triggered more soil respiration than exudates from undroughted plants. Importantly, this increased respiration compensated for the lower rates of root exudation in droughted plants. Our findings reveal a novel mechanism through which drought can continue to affect ecosystem carbon cycling, and a potential plant strategy to facilitate regrowth through stimulating microbial activity. These findings have important implications for understanding plant and ecosystem response to drought.